TRADITIONAL AND MODERN (GAT AND MZT) METHODS OF ASSESSMENT AND MONITORING OF SOIL FERTILITY - Khakimova Kamola Rakhimjonovna; Kholmirzayeva Durdona Shuhratbek kizi (Modern American Journals, 2025)
The article provides a systematic analysis of traditional and modern methods that are used to assess soil fertility and regularly monitor its condition. Traditional approaches consider agrochemical analysis, field experiments, fertilization, and soil-climatic zoning methods. Modern approaches highlight the role of geographic information systems (GAT) and remote sensing technologies (MZT) in spatial and temporal assessment of soil fertility indicators. Through the integration of GAT and MZT data, the possibilities of comprehensive assessment of the state of soil resources, early detection of degradation processes and justification of agricultural management decisions are provided with scientific and practical justification.
Keywords: Soil fertility, soil monitoring, GAT, remote sensing, agrochemical analysis, fertilization, spatial analysis, degradation.